2020
DOI: 10.1177/1129729820920108
|View full text |Cite
|
Sign up to set email alerts
|

A short bevel needle with a very thin tip improves vein puncture performance of peripheral intravenous catheters: An experimental study

Abstract: Background: Peripheral intravenous catheter placement is frequently unsuccessful at the first attempt. One suggested risk factor is a small vein size, because of the consequences of mechanical forces generated by the needle tip. We developed short bevel needles with a very thin tip and evaluated their puncture performance in two in vitro models. Methods: Peripheral intravenous catheters with a new needle ground using the lancet method (experimental catheter (L)) or backcut method (experimental catheter (B)) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…The bevel angle of the newly developed needles was 20°, and the penetration forces at the needle and catheter tips for the newly developed needles were low. [9] A previous study indicated that a decrease in skin resistance during insertion may reduce pain, and it is thought that the number of pain spots to be stimulated decreases because a low resistance reduces the extent of skin deformation during PIVC insertion. [17] The newly developed needles may be less painful than the existing needles because of their low penetration forces and resistance during PIVC insertion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bevel angle of the newly developed needles was 20°, and the penetration forces at the needle and catheter tips for the newly developed needles were low. [9] A previous study indicated that a decrease in skin resistance during insertion may reduce pain, and it is thought that the number of pain spots to be stimulated decreases because a low resistance reduces the extent of skin deformation during PIVC insertion. [17] The newly developed needles may be less painful than the existing needles because of their low penetration forces and resistance during PIVC insertion.…”
Section: Discussionmentioning
confidence: 99%
“…[17] The newly developed needles may be less painful than the existing needles because of their low penetration forces and resistance during PIVC insertion. [9,17] Therefore, differences between the newly developed and existing needles could have been detected if studies had been conducted considering different outcomes, such as pain scoring. Finally, external validity may be low because there were only a few patients with DIVA in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the previous study, the authors set the puncture speed at 50 mm/min. 35 Echo gel was applied to the surface of the model. The 40-mm long IJV embedded in the porcine shoulder was punctured in the midline, and deformation and displacement of the vessel during puncture was monitored by US (eZono-4000, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, needles for intravenous catheters need to have the shorter bevel length and the smooth bevel face, and the resistance forces must be measured until the bevel face of these needles including the catheters penetrates the object. Tanabe et al 35 developed a short bevel needle with a very thin tip and evaluated it using a phantom. The thin-tipped short bevel needle was 24-gauge (outer diameter: 0.55 mm) without any spiny projections on the bevel face and achieved successful puncture at smaller angles than the needles of conventional PIVCs, even when the insertion site on the polyvinyl chloride tube phantom was off-center.…”
Section: Introductionmentioning
confidence: 99%